Temperature Anisotropy Instabilities Stimulated by the Solar Wind Suprathermal Populations - Lazar, Marian; López, R.A.; Shaaban, Shaaban Mohammed; Poedts, Stefaan; Yoon, Peter Haesung; Fichtner, Horst (Frontiers in Astronomy and Space Sciences, 2022)
This review paper compiles recent results describing the effects of suprathermal populations present in space plasmas (up to a few keVs) on temperature anisotropy instabilities. Of particular interest are the electromagnetic cyclotron and firehose excitations, which play a major role in limiting temperature anisotropy, resulting, for instance, from the adiabatic expansion of the solar wind. Relying on a rigorous modeling and interpretation of the observed velocity distributions, both theoretical models and numerical simulations indicate a systematic stimulation of these excitations in the presence of suprathermal populations of electrons or protons. Moreover, the enhanced fluctuations react back on particles, and determine a faster and deeper relaxation of their anisotropy. The present comparative analysis suggests that previous studies, considering only quasi-thermal, low-energy populations may have significantly underestimated these excitations and their implications in various applications in space plasmas.